HASIL FUNGSIONAL PADA OSTEOARTRITIS LUTUT SETELAH INTERVENSI PROLOTERAPI DEKSTROSA: STUDI PILOT BERBASIS KEPARAHAN - Yose Waluyo; Sari Rajwani Artika; Insani Nanda Wahyuni; Endy Adnan; Budu; Agussalim Bukhari (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: Osteoarthritis currently remains a significant health problem due to its high prevalence and morbidity rate. Radiological examination is still used as a gold standard to determine the severity of knee osteoarthritis by using Kellgren-Lawrence grading. Dextrose prolotherapy has been known to be effective in treating pain in knee osteoarthritis, but none has compared the efficacy between mild and moderate-severe knee osteoarthritis. Objective: This study aims to compare the effectiveness of prolotherapy based on its radiological and symptomatic severity in knee osteoarthritis.Methods: In this pre-post study, the participants who underwent dextrose prolotherapy injection (25% intra-articular and 15% periarticular) for three sessions with four weeks intervals were grouped into mild (grade 1-2) and severe (grade 3-4) groups. Participants’ functional status was measured with Western Ontario and McMaster Universities’ arthritis index scores at baseline and week 12.Results: A total of 21 patients (average age 61.42 ± 8.33, BMI 26.81± 3.72) received three therapy sessions. Both groups had significantly better Western Ontario and McMaster Universities arthritis index scores than baseline (-22.57± 11.9; p = 0.002 and -15.42 ± 15.75; p = 0.003). All parameters were improved significantly (p <0.05) in both groups, except the stiffness score (p = 0.292; p = 0.057). There were no differences in functional outcome improvements in both groups (p > 0.05; CI 95%: -21.3 – 7.05).Conclusion: Prolotherapy effectively improves functional outcomes in all stages of knee osteoarthritis.